Effect of MoZrN Coating on a Steel XC100 - Abboudi, A.; Meddour, B.; Chermime, B.; Djebaili, H.; Brioua, M. (Металлофизика и новейшие технологии, 2016)
The zirconium nitride ZrN coatings are deposited on substrates of XC100 steel using physical vapour deposition (PVD) technique. Coatings based on nitrides of transition metals (Nb, Zr, Ti, V, ...) developed by PVD are known to increase the life of cutting tools, and so they naturally have seen a rapid industrial growth. It is possible to produce ZrN-coatings with variations of nitrogen partial pressure, the residual stresses, the thickness of the thin film, and the friction coefficient depending on the nitrogen content. Usage of nitrogen is a good way to enhance wear resistance and effectiveness in tribological applications.